ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKUNTANSI TERKOMPUTERISASI ATAS PENERIMAAN DAN PENGELUARAN KAS PADA CENTEC DON BOSCO COMORO - Nurasiah .; Ana Ivonia (Universitas Insan Pembangunan Indonesia, 2013)
ABSTRACT“Analysis and designing of a computerized accounting information system on the income and expenditure of cash at Centec Don Bosco”The designing of a computerized accounting information system is done at the Vocational training Centre Comoro Dili East Timor. At this very moment the administration work of receipts and payments by cash at Centec don Bosco is done manually. As a consequence the manual system incurs a lot of errors in the calculation, the data are not well organized and information delays are common. The objective of this research is to elaborate a computerized accounting system for the receipts and payments of cash at Don Bosco with the purpose of avoiding miscalculations, and to have a well organized data, a quick, accurate and timely access to the information needed. To achieve the intended goal it was important to have the analysis of the system of receipts and payments of the cash which includes receipts of the school fees, sales of the outcomes of the production units, subsidies from the government and donations;Second, analysis of payment procedures of general and special cashusage is also relevant and needed for the elaboration of a system that is more adequate to be used which can help better in the administration system. From the results of the designing it concludes that with the presence of a computerized accounting information system for the receipts and payments of the cash hopefully will reduce the negative effects of miscalculation, inefficiency of the management and administration of the cash. On theother hand the system would provide faster, accurate and effective services for the administration andmanagement of the funds at Don Bosco.Key words : Receipts/income and Payments/expenditure Centec Don Bosco.